Pengaruh Cash Holding, Profitabilitas, Leverage, Ukuran Perusahaan dan Kebijakan Dividen Terhadap Perataan Laba - Tiningsih, Tresna; Mubarok, Abdulloh (JABKO: Jurnal Akuntansi dan Bisnis Kontemporer, 2021)
The purpose of this research was to determine the effect of cash holding, profitablity, leverage, firm size and dividend policy on income smoothing. The method of data analysis used logistic regression analysis using the SPSS 22 program Secondary data were obtained from companies that are members of IDX30, using purposive sampling with a total sample of 60 samples for 4 periods. From the research conducted, it is found that there is no effect of the profitabilty, leverage and dividend policy variables on the old smoothing. Meanwhile, the cash holding and firm size variables have an effect on income smoothing.